PENGARUH MOTIVASI DAN KEPUASAN TERHADAP PERILAKU WIRAUSAHA PETERNAK AYAM BROILER POLA KEMITRAAN (CONTRACT FARMING) DI KOTA PEKANBARU - Maria Birgita Samosir; Cepriadi Cepriadi; Yulia Andriani (Fakultas Pertanian, Universitas Riau, 2019)
This study is aimed to know: (1) the motivation level of broiler breeder of contract farming in Pekanbaru city, (2) the level of satisfaction of broiler breeder in contract farming in Pekanbaru, (3) the level of entrepreneur's breeder behavior broiler farming pattern (contract farming) in Pekanbaru city and (4) analyze the influence of motivation and satisfaction on entrepreneur’s breederbehavior broiler farming pattern (contract farming) in Pekanbaru city. This study uses secondary data and primary data, secondary data obtained from the central statistical agency, the primary data obtained by distributing questionnaires to 40 respondents using convenience sampling technique. Data analysis is qualitative and quantitative, qualitative data is Likert-scale interpretation and multiple linear regression interpretation with SPSS 23 include: coefficient of determination, F test, and t test. In the motivation variable, Likert scale results show the value of motivation score is 3.69, it shows that breeders feel motivated in partnering. The value of satisfaction score is 3.63 which means in partnership of breeders included in the category of satisfaction. As for the behavioral variables obtained the average score is 3.25 indicates that the breeder is in the category quite capable in doing business. Multiple linear regression results show that the coefficient of determination is 0.742, meaning 74.2 percent of motivation and satisfaction relationships affect the behavior of broiler breeders, while the remaining 25.8 percent is influenced by other variables outside the equation model.